The Influence Of Authoritarian Leadership Style On Employee Innovation: Systematic Literature Review - Elita Darmasari; Emi Amalia; Ledi Diana; Sania, Sania (SEAN Institute, 2024)
In today's dynamic and competitive business landscape, innovation is the cornerstone of success in any industry. It is the employees within an organization who drive this innovation. A successful organization necessitates a leader with a unique leadership approach that cultivates an environment conducive to innovation, allowing teams to exceed past achievements. This study seeks to investigate the relationship between authoritarian leadership and employee innovation through an extensive review of existing literature. Using a literature review methodology, the research gathers data from Google Scholar. Previous studies have established a significant link between authoritarian leadership and employee innovation. The findings of this study could offer valuable insights for business professionals seeking a comprehensive understanding of the impact of authoritarian leadership in practical business settings. Moreover, this study will contribute to the current body of academic literature on leadership and employee innovation.